Abstract 099: Reversible Cerebral Vasoconstriction Syndrome Secondary to Weight Loss Patch: A Case Report​ - Karthik K. Narayanan; Brian B. Miremadi; Gunjan preet; Tikku George; Heer Hendry (Stroke: Vascular and Interventional Neurology)
Introduction Reversible Cerebral Vasoconstriction Syndrome (RCVS) is a clinico‐radiographical syndrome characterized by severe thunderclap headache and reversible multifocal arterial vasoconstriction1. RCVS can be spontaneous or related to a trigger such as vasoactive medication/supplements. There is no previous data on the association of weight loss patch formulation in the genesis of unexplained RCVS. Methods A woman in her 40s presented with five days of recurrent acute onset severe right frontal headaches after starting Thrive weight loss patch supplementation. Head CT showed right frontal lobe hemorrhage with bilateral SAHs (Figure1). Brain MRI redemonstrated hemorrhages, numerous scattered foci of restricted diffusion, and a large area of restricted diffusion in the left insular cortex (Figure 2). Cerebral angiogram showed diffuse multifocal narrowing with a ‘beads‐on‐a‐string’ appearance of the cerebral vasculature and no aneurysms (Figure 3). Thrive patch contains undisclosed amounts of sympathomimetics and vasoactive compounds. Given the history, clinical symptoms of recurrent thunderclap headaches, and angiographic findings, the diagnosis of RCVS was made. Brain MRA 3 months after discharge showed no areas of cerebrovascular focal stenosis (Figure 4). At 4 month follow up, she reported 90% improvement of her symptoms. Results We report a temporal relationship between RCVS in a woman in her 40s and usage of a Thrive weight loss patch, which contains green tea extract, L‐arginine, 5‐hydroxytryptophan (5‐HTP), and Yerba Mate. We believe this report represents the first case of RCVS triggered by a weight loss patch. Multiple compounds within the Thrive patch have vasoactive properties that may contribute to RCVS genesis. Epigallocatechin (component of green tea extract) and 5‐HTP are metabolic compounds with potent vasoactive properties. They are components of weight loss and SSRI/SNRI medications respectively. Numerous studies have documented a temporal relationship between their use and subsequent development of RCVS2,3. Resolution of RCVS is reported after their discontinuation. Only one other case in our literature review investigated a patch modality in a temporal relationship with RCVS. It reported development and resolution of RCVS six days after nicotine patch use and discontinuation4. While Thrive patch does not contain nicotine, this case provides a further avenue for exploration as to whether pharmacokinetics of a patch modality influences a patient’s presentation with RCVS, as all prior reports document oral ingestion of substances. Conclusion Clinicians should be aware of the role of weight loss patches in RCVS, and their use should be assessed in large RCVS cohorts to clarify the association described in this report.